2016
DOI: 10.1097/id.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platform Switching on Periimplant Crevicular Fluid Content During Early Wound Healing

Abstract: Purpose The objective of this study was to investigate the soft tissue response and periimplant crevicular fluid (PICF) content around platform-switched (PS) and platform-matched (PM) implants during early healing. Materials and Methods Non-smokers treatment planned to receive a single implant in 2 quadrants were recruited. Two-stage implant placement protocol with 1 PM and 1 PS implant was implemented. Periimplant probing depths (PDs), modified sulcus bleeding index, and plaque indices were recorded, and PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…PICF volume was not affected by the additional surgical procedure (data not shown). Compared to our previous study, 29 the PICF volume and the concentration of inflammatory cytokines were lower in this study. This could relate to the implant platform design because the implants used in this study were specifically designed to match their corresponding healing abutments and to establish either a PM or PS setting.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…PICF volume was not affected by the additional surgical procedure (data not shown). Compared to our previous study, 29 the PICF volume and the concentration of inflammatory cytokines were lower in this study. This could relate to the implant platform design because the implants used in this study were specifically designed to match their corresponding healing abutments and to establish either a PM or PS setting.…”
Section: Discussioncontrasting
confidence: 98%
“…Thus, PS implant does not seem to influence cellular responses related to early phases of healing despite of improved changes observed in some of the clinical parameters. These findings are mostly in agreement with our previous publication of similar study design 29 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, detectable but steady PISF levels of biochemical markers from 4 to 24 weeks in our study may reflect continuous maturation of peri‐implant mucosa and remodeling of CB in order to form and maintain the attachment in the neck area of the implant. The present findings were consistent with those from previous PISF studies regarding 6 to 12 weeks of early implant healing . The aforementioned studies also demonstrated that PISF levels of 8 molecules, including IL‐1β, G.CSF, MIP‐1β, IL‐6, IFN‐γ, IL‐8, IP‐10, and VEGF, in a similar manner observed in the present study, were high in early stages of peri‐implant wound healing and decreased generally between 4‐ to 8 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…To date, human trials heavily evaluated biomarker levels in PICF and their relationship with peri-implant disease [ 9 , 11 , 16 ]. However, studies focusing on biochemical analysis of PS with PICF biomarkers are limited [ 4 , 17 ]. This study is aimed at addressing the abovementioned research gap, focusing on biochemically investigating the association between marginal bone loss, peri-implant status, and RANKL, OPG, IL-1 β , and MCP-1 levels in PICF around PS and nonplatform-switched (NPS) implants in the first year of function.…”
Section: Introductionmentioning
confidence: 99%